2004
DOI: 10.1016/j.jasms.2003.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Wall-less sample preparation of μm-sized sample spots for femtomole detection limits of proteins from liquid based UV-MALDI matrices

Abstract: Previously, we introduced wall-less sample preparation (WaSP), technology that involves the use of an electrodynamic balance (EDB) to prepare m-sized sample spots for analysis by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). In that work we demonstrated the detection of femtomole quantities of a low molecular weight peptide and a hydrophobic ester (both Ͻ600 Da). Here we use WaSP to test the hypothesis that the use of small sample spot sizes and an instrument equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…Either static or programmed changes in the potentials applied to the electrodes comprising the EDB could be used to cause the droplet to be ejected when its m/z reaches a certain critical value, or those potentials can be set to retain the droplet within the EDB indefinitely. Importantly, the ejection of each droplet from the EDB can be controlled, and each droplet can be deposited at a known location on a substrate which allows subsequent manipulation and characterization of it [19]. Furthermore, translation of the substrate plate between droplet deposition events allows arrays of droplet residues to be formed [19], and it will be shown that they are ordered according to the m/z of the levitated droplet residues.…”
Section: Droplet Levitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Either static or programmed changes in the potentials applied to the electrodes comprising the EDB could be used to cause the droplet to be ejected when its m/z reaches a certain critical value, or those potentials can be set to retain the droplet within the EDB indefinitely. Importantly, the ejection of each droplet from the EDB can be controlled, and each droplet can be deposited at a known location on a substrate which allows subsequent manipulation and characterization of it [19]. Furthermore, translation of the substrate plate between droplet deposition events allows arrays of droplet residues to be formed [19], and it will be shown that they are ordered according to the m/z of the levitated droplet residues.…”
Section: Droplet Levitationmentioning
confidence: 99%
“…Importantly, the ejection of each droplet from the EDB can be controlled, and each droplet can be deposited at a known location on a substrate which allows subsequent manipulation and characterization of it [19]. Furthermore, translation of the substrate plate between droplet deposition events allows arrays of droplet residues to be formed [19], and it will be shown that they are ordered according to the m/z of the levitated droplet residues.…”
Section: Droplet Levitationmentioning
confidence: 99%
“…A number of groups, including our own, are exploring robotic devices as tools for increasing the reproducibility of submicroliter volumes of matrix solution deposited onto tissue sections (21)(22)(23)(24)(25). Microspots of matrix with diameters on the order of 200 -300 m can be generated with greater speed and precision than manual methods, allowing arrays of hundreds of matrix microspots to be deposited in a matter of minutes.…”
mentioning
confidence: 99%
“…23,24 Briefly, an electrode, referred to as the induction electrode, was positioned 3 mm from the orifice of the droplet dispenser. Variation of the DC potential applied to the induction electrode (IP f , the induction potential during droplet formation) proportionally varied the magnitude of the image charge imparted onto the forming droplets.…”
Section: Electrodynamic Charged Droplet Processing: Waspmentioning
confidence: 99%
“…Wall-less sample preparation (WaSP) 23,24 is a methodology that utilizes electrodynamic levitation technology, [25][26][27] in the form of a double-ring electrodynamic balance (EDB), to control the trajectories of picoliter volume charged droplets dispensed from a droplet-on-demand piezoelectric droplet dispenser. The levitated droplets can be deposited onto a target plate with high spatial accuracy, facilitating their analysis external to the EDB.…”
mentioning
confidence: 99%